Assessment of Vulnerability of Escape Building against Earthquake and Tsunami at Padang City - Billy Richard (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Earthquake occurred in September 30th, 2009 was the worst in the history of earthquake in West Sumatera. Damages of buildings were the main causes of human casualties at that time. The Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah, BPBD) of West Sumatera has conducted tsunami and earthquake mitigation, one of them is to prepare the Temporary Evacuation Site (TES) as a vertical-evacuation building allowing people to escape from tsunami attack in Padang City. This research was intended for evaluating and mapping the vulnerability potentials of all escape buildings to the earthquake and tsunami hazard. The investigation used Rapid Visual Screening method based on FEMA P-154 (Federal Emergency Management Agency) for assessing vulnerability of the building towards tsunami. According to the category of the obtained vulnerability potential, there were 50%, 33%, 10%, and 7% of escape buildings identified safe, non-structurally vulnerable, structurally vulnerable from earthquake, and vulnerable to tsunami, respectively.